2010
DOI: 10.1007/s10822-010-9396-7
|View full text |Cite
|
Sign up to set email alerts
|

In silico strategies for the selection of chelating compounds with potential application in metal-promoted neurodegenerative diseases

Abstract: The development of new strategies to find commercial molecules with promising biochemical features is a main target in the field of biomedicine chemistry. In this work we present an in silico-based protocol that allows identifying commercial compounds with suitable metal coordinating and pharmacokinetic properties to act as metal-ion chelators in metal-promoted neurodegenerative diseases (MpND). Selection of the chelating ligands is done by combining quantum chemical calculations with the search of commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Full geometry optimizations and harmonic frequency calculations were performed using DFT with the nonlocal hybrid B3LYP , functional, a well-tested functional that has been successfully used for a wide variety of systems, including open-shell Cu(II) complexes with saturated coordination environments and similar spin density distributions. Additionally, our previous study on the chelating properties of different ligands toward Cu(II) and Zn(II) showed good agreement with the observed experimental trends. All calculations were carried out using the following basis sets: For Cu, we used the Watcher’s primitive set (14s9p5d), supplemented with one s, two p, and one d diffuse function and one f polarization function, the final basis set being (15s11p6d1f)/[10s7p4d1f]; for iodine, we used the quasi-relativistic effective core potential (ECP) of Hay and Wadt to represent the innermost electrons and the standard double-ζ LANL2DZ set associated to the ECP for the valence and outermost core orbitals; and for H, C, N, O, and S, we used the standard 6-31++G(d,p) basis set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full geometry optimizations and harmonic frequency calculations were performed using DFT with the nonlocal hybrid B3LYP , functional, a well-tested functional that has been successfully used for a wide variety of systems, including open-shell Cu(II) complexes with saturated coordination environments and similar spin density distributions. Additionally, our previous study on the chelating properties of different ligands toward Cu(II) and Zn(II) showed good agreement with the observed experimental trends. All calculations were carried out using the following basis sets: For Cu, we used the Watcher’s primitive set (14s9p5d), supplemented with one s, two p, and one d diffuse function and one f polarization function, the final basis set being (15s11p6d1f)/[10s7p4d1f]; for iodine, we used the quasi-relativistic effective core potential (ECP) of Hay and Wadt to represent the innermost electrons and the standard double-ζ LANL2DZ set associated to the ECP for the valence and outermost core orbitals; and for H, C, N, O, and S, we used the standard 6-31++G(d,p) basis set.…”
Section: Methodsmentioning
confidence: 99%
“…Thermodynamic corrections have been obtained assuming an ideal gas, unscaled harmonic vibrational frequencies, and the rigid rotor approximation by standard statistical methods . Solvation effects were modeled through single-point energy calculations at the same level of theory, with water as solvent, using the self-consistent field polarizable continuum model, COSMO. , To compute the free energy of the [Cu(H 2 O) 4 ] 2+ + 2HL → [Cu(L) 2 ] + 4H 2 O + 2H + reaction in water solution (Δ G sol ), we have followed the strategy adopted by some of us in previous works , using the experimental free energy values for the solvation of water and H + (Δ G Solv(H 2 O) = −6.31 kcal mol –1 and Δ G Solv(H + ) = −265.9 kcal mol –1 , respectively). Because this reaction occurs in solution, the entropy obtained in gas phase was converted from 1 atm to 1 M by subtracting the R ln(V1/V2) cal K –1 mol –1 term to account for the volume change between the two states at 298 K .…”
Section: Methodsmentioning
confidence: 99%
“…Compound-(E)- N 1, N 1-Dimethyl- N 4-(pyridin-2-ylmethylene)benzene-1,4-diamine has been shown to modulate reactive oxygen species (ROS) production, metal-induced Aβ aggregation, and neurotoxicity in vitro ( Hindo et al, 2009 ). The drug Deferiprone used in treatment of thalassaemia can be taken as lead compound for the development of MTDL for treating AD because it has moderate to strong affinity for iron, copper and zinc, and low molecular weight makes it easily to modified into multi-functional active molecule ( Rodríguez-Rodríguez et al, 2011 ). The study suggested that Aβ aggregation is inverted in the occurrence of Cu +2 and Zn +2 chelators.…”
Section: Development Of Multi-functional Anti-alzheimer Agentsmentioning
confidence: 99%
“…34,35,37 Traditionally, numerous studies have demonstrated that the prediction of drug passage into the CNS via passive diffusion can be estimated using a simple relationship, which establishes the crucial role of polarity and hydrogen bonding capability. 20,54 The reported log BB values, 20 summarized in Table 1, are based on computationally derived physicochemical descriptors such as the calculated octanol-water partition coefficient (c log P) and the topological surface area (TPSA). 20,54 The reported log BB values, 20 summarized in Table 1, are based on computationally derived physicochemical descriptors such as the calculated octanol-water partition coefficient (c log P) and the topological surface area (TPSA).…”
Section: Cell Viability In Bend3 Cellsmentioning
confidence: 99%